Lao People's Democratic Republic : Technical Assistance Report-Report on National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
A technical assistance mission was conducted during July 2-13, 2018 to support measurement of Lao PDR's national accounts statistics. The mission assisted with the development of a quarterly GDP time series, reviewed the published annual GDP time series, and developed recommendations to continue improving national accounts statistics compiled by the Lao Statistics Bureau (LSB). The mission built upon previous national accounts statistics missions conducted in April 2017 and January 2018.